A new method for preparing photocatalytic cement-based materials and the investigation on properties and mechanism. (March 2021) - Geng, Zhi; Xin, Mingyu; Zhu, Xutong; Xu, Haoyu; Cheng, Xin; Wang, Dan
Abstract: An application of nano-photocatalyst in cementitious materials may induce the improvement of photocatalytic property and mechanical strength, however, the problems of dispersion and high cost of nano-photocatalyst in cementitious materials lead to their negative effect. Photocatalyst can be obtained by low-cost photocatalyst precursors under high-temperature reaction condition, and highly dispersed into cement-based materials. The principle objective of the study is the preparation of photocatalytic cement-based materials by inducing photocatalyst precursors using the autoclaving method of cement, and their photocatalytic property and mechanical strength were investigated. The results show that photocatalysts were formed in cementitious materials via a special synthesis method and show excellent photocatalytic property on RhB degradation and NOx removal under visible light irradiation, and BJH calculations provided a perspective to analyze the effect of pore structure on photocatalytic performance. The compressive strength and flexural strength of cement prisms modified with photocatalyst favored a better performance after autoclaving at early age. The strengthening mechanism of cement-based materials was explored by some characteristics of prepared samples, such as changes of mineral phases and types of hydration products, morphology of fracture surface and polymerization of silicon oxygen tetrahedron. The experimental results of this study indicate a synergic effect between the nano-sized photocatalyst and autoclaving, and low concentration photocatalyst precursors (1.5 wt% Bismuth source) and autoclaving can both endow cement-based material with impressive strength performance on the premise of the basic property of photocatalysis. Highlights: Cementitious materials formed via a special synthesis method showed excellent photocatalytic property. Compressive strength and flexural strength are increased rapidly with autoclaving at early age. The mechanism were provided by the composition and morphology analysis.